Calorie restriction increases muscle mitochondrial biogenesis in healthy humans. - Anthony E Civitarese; Stacy Carling; Leonie K Heilbronn; Mathew H Hulver; Barbara Ukropcova; Walter A Deutsch; Steven R Smith; Eric Ravussin; CALERIE Pennington Team (PLoS Medicine)
Background Caloric restriction without malnutrition extends life span in a range of organisms including insects and mammals and lowers free radical production by the mitochondria. However, the mechanism responsible for this adaptation are poorly understood. Methods and findings The current study was undertaken to examine muscle mitochondrial bioenergetics in response to caloric restriction alone or in combination with exercise in 36 young (36.8 +/- 1.0 y), overweight (body mass index, 27.8 +/- 0.7 kg/m(2)) individuals randomized into one of three groups for a 6-mo intervention: Control, 100% of energy requirements; CR, 25% caloric restriction; and CREX, caloric restriction with exercise (CREX), 12.5% CR + 12.5% increased energy expenditure (EE). In the controls, 24-h EE was unchanged, but in CR and CREX it was significantly reduced from baseline even after adjustment for the loss of metabolic mass (CR, -135 +/- 42 kcal/d, p = 0.002 and CREX, -117 +/- 52 kcal/d, p = 0.008). Participants in the CR and CREX groups had increased expression of genes encoding proteins involved in mitochondrial function such as PPARGC1A, TFAM, eNOS, SIRT1, and PARL (all, p < 0.05). In parallel, mitochondrial DNA content increased by 35% +/- 5% in the CR group (p = 0.005) and 21% +/- 4% in the CREX group (p < 0.004), with no change in the control group (2% +/- 2%). However, the activity of key mitochondrial enzymes of the TCA (tricarboxylic acid) cycle (citrate synthase), beta-oxidation (beta-hydroxyacyl-CoA dehydrogenase), and electron transport chain (cytochrome C oxidase II) was unchanged. DNA damage was reduced from baseline in the CR (-0.56 +/- 0.11 arbitrary units, p = 0.003) and CREX (-0.45 +/- 0.12 arbitrary units, p = 0.011), but not in the controls. In primary cultures of human myotubes, a nitric oxide donor (mimicking eNOS signaling) induced mitochondrial biogenesis but failed to induce SIRT1 protein expression, suggesting that additional factors may regulate SIRT1 content during CR. Conclusions The observed increase in muscle mitochondrial DNA in association with a decrease in whole body oxygen consumption and DNA damage suggests that caloric restriction improves mitochondrial function in young non-obese adults.